Coding Bootcamps for Youth Employment : Evidence from Colombia, Lebanon, and Kenya - World Bank (World Bank, Washington, DC, 2018)
Coding bootcamps are intensive short-term programs designed to train participants in programming skills to make them immediately employable. They combine characteristics of traditional vocational training programs with the intensity of military bootcamps for new recruits, intermingling socio emotional and tech skills learning in an intense and experiential manner, in what could be referred to as skills accelerators. The authors refer to coding bootcamps in this report as the ready-to-work model. The initiative aims to collect and share examples and lessons of bootcamps in emerging markets, and measure the impact of bootcamp training on youth employment in selected countries. The program seeks to establish a framework of best practice for future projects in technology upskilling in the developing world. This report highlights the results of a randomized controlled trial (RCT) carried out in Medellín (Colombia), complemented with qualitative studies in Beirut (Lebanon) and Nairobi (Kenya). This report is arranged as follows: Chapter 1 starts with introduction; Chapter 2 describes the intervention in Medellín,including the experimental allocation of training slots to the bootcamp; Chapters 3 and 4 present the qualitative studies in Beirut and Nairobi; The main findings from the three interventions are presented in Chapter 5; and lessons for future impact evaluations are described in Chapter 6.